Effect of Three Organic Manures on some Physical and Chemical Properties of Khashm Elgirba Soil Series - A. Ali, Zaheeruddin; I. Adam, Adam (Gezira Journal of Agricultural Science, 2021)
The effect of farmyard manure (FYM), filtermud (FM), and bagasse on some physical and chemical properties of Khashm Elgirda soil series was studied in 1999-2000. Each of the organic manures was applied at a rate of 0,15,30,45,60, and 75 t ha -1 in a RCBD with four replications. The organic manures were incorporated into the soil using hand tools. The study showed that increasing the rate of each of the applied manures resulted in a highly significant reduction in the soil bulk density and consequently a highly significant increase in both total soil porosity and soil moisture. Bagasse was the most effective in reducing the soil bulk density followed by FYM and lastly FM. The study also indicated that increasing rates of application of each of the tested manures resulted in small increments of both exchangeable potassium and organic carbon. However, the investigation did not show any noticeable increase in total soil nitrogen.